Internalization of islamic education values through qur’anic tadabbur for emotional detox and islamic self-healing - Sumayah; Evidatul Nur Maulida; Herliyana Isnaeni; Mohamad Ardin Suwandi (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
This study discusses the concept of emotional detox as an adaptive process to cleanse accumulated emotional burdens, with a psychological perspective emphasizing emotion regulation through awareness, reinterpretation and response modification. This concept is integrated with Al-Qur'an reflection as a form of transformative literacy involving deep contemplation of sacred verses to reduce anxiety and build emotional resilience. In the context of Islamic self-healing in the digital era, tadabbur emerges as a technology-supported mechanism for inner healing, through interactive applications and reflective content on social media that function as digital detox to overcome information overload and emotional fatigue.